(untitled) (Psychology Travelogs, 2025)
The article examines the impact of the COVID-19 pandemic on the cognitive sphere of young people, particularly students, who experienced significant changes in the educational process during quarantine restrictions and continued to be affected during the full-scale invasion of Ukraine. Special attention is given to the influence of distance and hybrid learning formats, as they transformed the educational environment and generated new challenges for students’ cognitive resources. The study addresses issues of cognitive dysfunction, the emergence of digital fatigue and information overload, which complicate knowledge acquisition, as well as the questions of psychological and cognitive resilience. As a result of the systematization of current research, it has been established that prolonged exposure to the online environment provokes emotional exhaustion and induces changes in cognitive functioning. The article analyzes the effects of unequal access to digital resources, the importance of social support, and the necessity of developing self-regulation skills and the ability to organize personal space, since these factors significantly affect educational and psychological imbalances, as well as students’ ability to adapt quickly to the requirements of distance and hybrid learning and to restore cognitive functioning. The paper is devoted to understanding the consequences of the pandemic for cognitive changes in students and emphasizes the importance of rethinking the educational paradigm in light of the introduced transformations. The formation of cognitive resilience and digital hygiene, as well as the development of critical thinking skills, are considered key factors for the success of modern higher education. These aspects can significantly mitigate the negative consequences of the pandemic and the changes faced by students, as well as serve as a resource for enhancing young people’s adaptability in the event of future crises.